2005
DOI: 10.1002/marc.200500629
|View full text |Cite
|
Sign up to set email alerts
|

A Polymer Composite Film with Reversible Responsive Behaviors

Abstract: Summary: A responsive polymer composite film was generated by the use of reversibly switchable surface morphology of polystyrene‐block‐poly(methyl methacrylate) (PS‐b‐PMMA) films in response to different block selective solvents on the rough isotactic poly(propylene) (i‐PP) substrate. The maximum difference of the water contact angle of the composite films increased from 22.6° of PS‐b‐PMMA films on the smooth substrate to 42.6° when they were treated by PS and PMMA selective solvents, respectively. The mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…2a). It is reverse to the general facts that the CA on low roughness region of a surface with a gently changed gradient is lower than that on high roughness region for a native hydrophobic material, such as polystyrene, polyethylene, and so on [14][15][16][17][18]. In the previous work [14a], a gradient surface was also fabricated, which wettability can change slowly from hydrophobicity (water CA, 99.6 • ± 0.7 • ) to superhydrophobicity (water CA, 165.8 • ± 0.2 • ) along the length of 12 mm.…”
Section: A Unique Phenomenon About Water Drops On the Surfacementioning
confidence: 85%
See 1 more Smart Citation
“…2a). It is reverse to the general facts that the CA on low roughness region of a surface with a gently changed gradient is lower than that on high roughness region for a native hydrophobic material, such as polystyrene, polyethylene, and so on [14][15][16][17][18]. In the previous work [14a], a gradient surface was also fabricated, which wettability can change slowly from hydrophobicity (water CA, 99.6 • ± 0.7 • ) to superhydrophobicity (water CA, 165.8 • ± 0.2 • ) along the length of 12 mm.…”
Section: A Unique Phenomenon About Water Drops On the Surfacementioning
confidence: 85%
“…Since r is always larger than unity, the surface roughness enhances both the hydrophilicity of hydrophilic surfaces and the hydrophobicity of hydrophobic ones. The Wenzel's theory has been proved by a great number of experimental results [15][16][17][18]. For example, Erbil et al increased hydrophobicity of PP to superhydrophobicity by increasing its surface roughness [15d].…”
Section: Introductionmentioning
confidence: 98%
“…Lu et al [112] demonstrated a change of the water contact angle from 22.6 to 42.68 when films were treated with solvents selective for the PS or PMMA units, respectively. This behaviour is illustrated in Figure 16.…”
Section: Environmental Switchingmentioning
confidence: 98%
“…Two parallel studies by Lu et al [112] and Zhao et al [113] developed reversibly switchable surfaces from polystyrene-blockpoly(methyl methacrylate) (PS-b-PMMA), which respond to block-selective solvents. Lu et al [112] demonstrated a change of the water contact angle from 22.6 to 42.68 when films were treated with solvents selective for the PS or PMMA units, respectively.…”
Section: Environmental Switchingmentioning
confidence: 99%
“…For PMMA, various approaches have been used to turn its weakly hydrophobic nature into super-hydrophobic, including replicating, imprinting, and mesh-assisted via mold [2][3][4][5]; lithography and soft-lithography [6][7][8][9], plasma etching [10][11][12][13][14], and vapor deposition [15]; solutions of mixing two or more different kinds of powders [16][17][18][19][20][21][22][23][24][25][26], and different powder grain sizes [27][28][29][30]; fluoride coated surfaces [31,32]; and electrospinning and electrospraying [33]. In contrast, we have been concentrated on developing lower cost and simpler methods.…”
Section: Introductionmentioning
confidence: 99%